The purposes of school Physical Education - Dalva Marim Beltrame (Journal of Physical Education (Maringá), 2008)
The aim of this paper was to analyze the purposes of school physical education in Brazil, through a bibliographical survey of the propositions presented by authors who dealt with this issue along the past century. It may be pointed out that school physical education sometimes has been regarded as a strategy and on other occasions as a theme, according to the perception each author had of his/her own time and ideological commitment. It has always been part of the school education though its contents have been modified, enlarged or excluded along the years. Finally it may be concluded that, in spite of the intense debate registered in the surveyed books, the purposes of school physical education are still open for further discussion.